The Correlation Between Adiponectin Levels With C-Reactive Protein in Adult Obese Non-Diabetic Among Staffs of DR. M. Djamil Hospital Padang - Dian Eka Putri; Rismawati Yaswir; Desywar Desywar; Efrida Efrida (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
The adiponectin and C-reactive protein (CRP) are markers of chronic low-grade inflammation related to obesity. This study aims to determine a correlation between adiponectin level and CRP level in adult obese individuals. This study was analyzed with a cross-sectional design of 55 subjects at Dr. M Jamil Central Hospital Padang from January to September 2019. The subjects included were type 1 obese (25≤BMI≤29.9 kg/m2) and type 2 obese (BMI 30.0 kg/m2). Enzyme-linked immunoassay (ELISA) was used to measure adiponectin and High Sensitivity C-Reactive Protein (Hs-CRP) levels. Univariate statistical analysis is processed and presented in distribution, frequency, mean (standard deviation), median (minimum-maximum value). Bivariate data were analyzed using the Pearson correlation test, significant if p<0.05. The study consists of 16 males and 39 females. The mean age was 35 years old (the range 23 to 57 years old), the mean BMI was 30.8 (4.5) kg/m2. This study consists of 28 subjects, type 1 obese and 27 types II obese. The mean adiponectin level in type 2 obese is lower than in type 2 obese groups. The mean CRP levels are high in all populations. Pearson ln-adiponectin and CRP correlation test in the entire population: r =-0.105 (p=0.444).